Autonomia financeira e eficiência dos gastos públicos nos estados brasileiros - Garcez Neto, Joaquim Gomes (2015)
This paper promoted a spending efficiency analysis and investment of state governments from annual data of the National Treasury Secretariat (STN) for the financial years 25 federal units of Brazil between 2009 and 2013. Econometric Models for efficiency measures spending and public investment was estimated and the result showed that the financial autonomy is the means to achieving greater efficiency in terms of state budget execution.